ESRRG and PERM1 Govern Mitochondrial Conversion in Brite/Beige Adipocyte Formation - Müller, Sebastian; Perdikari, Aliki; Dapito, Dianne H.; Sun, Wenfei; Wollscheid, Bernd; Balaz, Miroslav; Wolfrum, Christian (Frontiers in Endocrinology, 2020)
When exposed to cold temperatures, mice increase their thermogenic capacity by an expansion of brown adipose tissue mass and the formation of brite/beige adipocytes in white adipose tissue depots. However, the process of the transcriptional changes underlying the conversion of a phenotypic white to brite/beige adipocytes is only poorly understood. By analyzing transcriptome profiles of inguinal adipocytes during cold exposure and in mouse models with a different propensity to form brite/beige adipocytes, we identified ESRRG and PERM1 as modulators of this process. The production of heat by mitochondrial uncoupled respiration is a key feature of brite/beige compared to white adipocytes and we show here that both candidates are involved in PGC1α transcriptional network to positively regulate mitochondrial capacity. Moreover, we show that an increased expression of ESRRG or PERM1 supports the formation of brown or brite/beige adipocytes in vitro and in vivo. These results reveal that ESRRG and PERM1 are early induced in and important regulators of brite/beige adipocyte formation.